Peningkatan Kemandirian Belajar Siswa dengan Menerapkan Pembelajaran STEAM di Sekolah Dasar - Dini Xena Dista; Rusdial Marta; Mufarizuddin Mufarizuddin (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
This study aims to describe the increase in learning independence of elementary school students by applying STEAM learning. The research method used is the classroom action research method. This research was conducted in two cycles, where each cycle went through four stages, namely the planning, implementation, observation, and reflection stages. The subjects of this study were the fourth-grade students of SDN 004 Bangkinang Kota totaling 13 people consisting of 6 male students and 7 female students. The results showed that there was an increase in student learning independence from pre-action to cycle 1 of 6,01%. The increase in student learning independence also shows an increase from cycle 1 to cycle 2 by 20,44%. The overall increase in student learning independence is 26,44%. STEAM learning must continue to be carried out to increase the learning independence of elementary school students. Teachers need continuous assistance in order to apply the STEAM learning model according to the suggested steps.